Billy Elliot - Daldry, Stephen; Hall, Lee,|d1966- (Universal Studios ; distributed in the Philippines by MagnaVision, 2001)
Eleven-year-old miner's son Billy Elliot is on his way to boxing lessons when he stumbles upon a ballet class. Billy secretly joins the class, knowing that his blue-collar family would never understand.